PENGARUH PEMBIAYAAN MURABAHAH, MUSYARAKAH DAN MUDHARABAH TERHADAP PROFITABILITAS PADA PT. BANK SYARIAH MANDIRI PERIODE 1999-2018 - Rr. Dimas Veronica Priharti; Tati Herlina; Farah Sutria Kholis (STIE DWI SAKTI BATURAJA, 2021)
Based on the results of data analysis using multiple linear regression calculations, the t count obtained for Murabahah Financing (X1) with Profitability is 4,096 means that there is an influence between Murabahah Financing (X1) on Profitability. T count value obtained for Musyarakah Financing (X2) with profitability is -1,626 means there is an influence between Musyarakah Financing (X2) on Profitability. The t count obtained for Mudharabah Financing (X3) with Profitability is 1,683 means that there is an influence between Mudharabah Financing (X3) on Profitability. While testing together has a significant influence on Murabahah, Musyarakah and Mudharabah financing variables on Profitability with F count of 7,676. While the coefficient of determination Adjusted R square value is 0.513, this means that the percentage contribution of Murabahah (X1), Musyarakah (X2) and Mudharabah (X3) variables on profitability is 513% while the remaining 487% is influenced by other variables not examined in this study.